Pembebasan sebagai tema perjuangan: Analisis terhadap karya kreatif Hamka - Yus'aiman, Jusoh @ Yusoff (2014)
Liberation is one of the major objectives in the teaching of Islam as delivered by Prophet Muhammad SAW. The struggle for liberty has been continued by scholars such as Haji Abdul Malik Karim Amrullah (HAMKA). As a renowned Malay Archipelago scholar, he has produced a large number of literary works including those of both creative and scholar in nature. Liberation is an important theme that has emerged in his literatures, especially in his creative works. Therefore, this study analyzes the theme of liberation in HAMKA‟s creative works. The objective of this study is to identify the liberation of faith found in his creative works. Besides, another objective of this study is to examine the liberation of thinking and analyze the social liberation of creative works that he has produced. The study uses qualitative method focusing on content analysis technique in HAMKA‟s creative works both intrinsically and extrinsically. Two approaches are used, namely the moral approach that emphasizes on themes and enquiries in the creative works as well as a narrative approach. All of HAMKA‟s creative works comprise of six novels and three short story anthologies are analyzed thoroughly and comprehensively. The finding of the study shows that HAMKA‟s creative works are rich with the liberation theme covering liberation in terms of faith, thoughts and social. The liberation of faith focuses on the purification of tawhid. In terms of thoughts, it involves the liberation from blind acceptance, materialistic desires and lust. Social liberation, on the other hand, includes the efforts in the implementation of justice, emancipation from Minangkabau customs and the liberation of marginalized groups. The study also finds that the theme of liberation in HAMKA‟s creative works matches with Asghar Ali Engineer Liberation Theory applied. HAMKA could effectively deliver the theme of liberation in his creative works indeed. This study has proven that liberation is a core component in HAMKA‟s da’wah manifested through creative works that he has produced. It also enriches the study of the corpus of knowledge, especially in the genre of Islamic Malay Archipelago literature.